2017
DOI: 10.1080/01916122.2017.1356760
|View full text |Cite
|
Sign up to set email alerts
|

Cedrus atlantica pollen morphology and investigation of grain size variability using laser diffraction granulometry

Abstract: The morphology and size variability of pollen grains of Cedrus atlantica were investigated using a novel approach employing laser diffraction granulometry. We provide new insights into size variability and present high-quality light microscopy (LM) and scanning electron microscopy (SEM) imagery of Cedrus atlantica pollen. Grains have an average size of 59.1 § 4.0 mm, measured on millions of grains from 91 samples. Analysis showed there is high variability of grain size within individual samples, although varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that the productivity, the interval of production, and the release of pollen strobili depend on year, population, and species [58,59] while for Atlas cedar Smith [60] noted "irregularity" with the development of pollen and Bell et al [32] found no significant relationships between climate, soil nutrient availability, and pollen size. Besides buffering against these unpredictable factors, we argue that the age affects the branch sexuality sensitivity of Cedrus to shade and must be considered at the individual tree level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the productivity, the interval of production, and the release of pollen strobili depend on year, population, and species [58,59] while for Atlas cedar Smith [60] noted "irregularity" with the development of pollen and Bell et al [32] found no significant relationships between climate, soil nutrient availability, and pollen size. Besides buffering against these unpredictable factors, we argue that the age affects the branch sexuality sensitivity of Cedrus to shade and must be considered at the individual tree level.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies have been made on the cedar response to environment and have furthermore shown that (1) the better light and water availability induce higher growth rates, wider tree rings, and lower leaf area index in Lebanon Cedar [29], (2) the low precipitation during summer limits tree growth on Lebanon Cedar [30], (3) the adverse climatic conditions and soil fertility affect the polycyclism and annual shoot length in Cedrus [26], (4) the low nutrient availability reduces the growth unit size, life duration of branch, and shoot number and modifies the axillary product category and their distribution in C. atlantica [24], (5) the high water status and low global radiation increase the duration of the daily growth period in C. atlantica [23], (6) the dry set decreases height growth for C. atlantica more than C. Brevifolia and vice versa in the well-watered set [31] proving that C. atlantica is the last drought-tolerant compared to C. brevifolia and C. libani. Recently, Bell et al [32] found that variability of pollen grain size and production within individual samples of Atlas cedar may result from the irregular development of pollen without any evidence for climatic and nutrient influences and concluded that it is influenced by a number of complex factors. Consequently, they underscore the need for further investigation of the complex controls on pollen and strobili development because it would not be possible to use this for the moment as a proxy for environmental reconstitution and cedar conservation.…”
Section: Introductionmentioning
confidence: 99%
“…C. atlantica is a climatically sensitive montane conifer endemic to North Africa of great biogeographical interest. Cedrus pollen are large (59.1 ± 4.0 µm) and easily identifiable, facilitating their study for isotope analysis (Bell et al, ). Furthermore, as an autumn pollinating species, pollen develops over the summer, making it possible to infer a summer climate signal (Bell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pollen grains, like other plant tissues and cells, produce UACs as a repair and defense mechanism against UV-B exposure [ 52 ]. The content and variation of UACs after exposure to UV-B differ between pollen grains of different species and even between pollen grains of different genotypes [ 53 ]. Therefore, the content of UACs is a useful tool to monitor the effect of UV-B radiation on pollen grains [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the content of UACs is a useful tool to monitor the effect of UV-B radiation on pollen grains [ 37 ]. Indeed, UAC production in pollen grains has been shown to increase as a direct response to increased UV-B exposure [ 53 , 54 ]. Day and Demchik [ 18 ] reported a strong increase in UACs after UV-B treatment in Brassica napus pollen grains.…”
Section: Discussionmentioning
confidence: 99%